Meta-Analysis: Relationship between Alcohol Consumption and Age on Obesity in Adults - Ayu Novita Wulandari; Amin Nur Hanida (Masters Program in Public Health, 2022)
Background: Obesity has become a serious public health problem in both developed and developing countries. Excessive alcohol consumption in adults is a global problem that needs further investigation. The adult age group has a high enough risk of being overweight and obese. The purpose of this study was to estimate the relationship between alcohol consumption and age on obesity.Subjects and Method: This research is a systematic study and meta-analysis. The articles used in this study were obtained from the Pubmed and Google Scholar databases. The articles used are articles that have been published from 2012-2022. The search for articles was carried out by considering the eligibility criteria determined using the PICO model. P= adults, I= alcohol consumption and middle age, C= no alcohol consumption and early adulthood, O= obesity. The keywords to search for articles were as follows: “Alcohol Consumption” OR “Alcohol Intake” AND “Age” AND “Obesity” OR “Body Mass Index” and “aOR”. The articles included in this study are full text articles with a cross-sectional research design. Articles were collected using the PRISMA flow chart. Articles were analyzed using the Review Manager 5.3 application.Results: There are 13 articles consisting of 2 studies from North America (Nicaragua, United States), 1 study from South America (Brazil), 1 study from Europe (Portugal), 7 studies from Africa (Ethiopia, Zimbabwe, Ghana), and 2 studies from Asia (Cambodia, Thailand) were included in this meta-analysis. 7 cross-sectional studies showed that alcohol consumption increased the risk of obesity in adults 2.05 times compared with those who did not consume alcohol (aOR= 2.05; 95% CI= 1.26 to 3.33; p= 0.004). A meta-analysis of 7 cross-sectional studies showed that middle age increased the risk of obesity 2.57 times compared with early adulthood (aOR= 2.57; 95% CI= 1.99 to 3.30; p = 0.001).Conclusion: Alcohol consumption and age are risk factors for obesity in adults. Keywords: alcohol consumption, age, obesity, adults Correspondence:Ayu Novita Wulandari. Applied Graduate School, Prosthetic Orthotic, School of Health Sciences, Ministry of Health Surakarta. Jl. Letjen Sutoyo Mojosongo Surakarta 57127, Central Java. Email: ayunovitawulandari98@gmail.com. Mobile :082281301325.